Endoscopic navigation system with extended field of view using augmented reality technology - Bong, Jae Hwan; Song, Hyun‐jong; Oh, Yoojin; Park, Namji; Kim, Hyungmin; Park, Shinsuk (The international journal of medical robotics + computer assisted surgery, 2018)
Background While endoscopic skull base surgery (ESBS) has emerged as an alternative surgical option, the limited field of view of the endoscope may lead to the surgeon's fatigue and discomfort. Methods The developed navigation system includes extended augmented reality (AR), which can provide an extended viewport to a conventional endoscopic view by overlaying 3D anatomical models generated from preoperative medical images onto endoscope images. To enhance the accuracy of the developed system, we adopted state‐of‐the‐art endoscopic calibration and tracking techniques based on an optical tracking system. Results The mean spatial errors of AR was ~1 mm, which falls in the acceptable range of accuracy for ESBS. For the simulated surgical tasks with the developed system, the number and duration of error events were decreased. Conclusions The results show that the human subject can perform the task more precisely and safely with the developed AR‐based navigation system than with the conventional endoscopic system.